(untitled) (Journal of the College of Basic Education, 2022)
Allama Mohammed Iqbal is the most celebrated poet, thinker, and philosopher during the first half of the 20th century. He was from British India now Pakistan, who has wrote very powerful poems and essays about religion and morality of Islam. His poems are revolutionary in spirit and they can be read as a compliant about the lethargy of the Muslims and the decadence of their civilization. This paper sheds the light on the two major issues of life, religion and science. The poet deals with the reality of religion in his own philosophy, moreover the researcher tries to show the poet’s attitude towards the science of the west in relation to religion and the construction of the ideal self.